Geological, Ocean, and Mineral CO2 Sequestration Options: A Technical Review - Voormeij, Danae; Simandl, George (Geoscience Canada, 2004)
SUMMARY Of the six greenhouse gases (GHG) covered by the Kyoto protocol, carbon dioxide (CO2) is the greatest contributor to Canada's total GHG emissions. Fossil fuel combustion is the main source of anthropogenic CO2, and it currently supplies over 85% of the global energy demand. Worldwide, an effort for reduction of CO2 emissions aims at increased efficiency of fossil energy usage, development of energy sources with lower carbon content and increased reliability on alternative energy sources such as wind, solar, geothermal and nuclear. However, to meet the objectives of the Kyoto agreement, CO2 sequestration methods may be needed. In this review, the methods that we will cover are storage in oil and gas reservoirs, in deep coal seams, in deep saline aquifers, in deep ocean, in salt caverns, and mineral carbonation. Each of these methods has its weaknesses and strengths.